Myeloid-Derived Suppressor Cells in COVID-19: The Paradox of Good - Grassi, Germana; Notari, Stefania; Gili, Simona; Bordoni, Veronica; Casetti, Rita; Cimini, Eleonora; Tartaglia, Eleonora; Mariotti, Davide; Agrati, Chiara; Sacchi, Alessandra (Frontiers in Immunology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the causative agent of the ongoing coronavirus disease 2019 (COVID-19) pandemic. Viral replication in the respiratory tract induces the death of infected cells and the release of pathogen- associated molecular patterns (PAMPs). PAMPs give rise to local inflammation, increasing the secretion of pro- inflammatory cytokines and chemokines, which attract immune cells from the blood into the infected lung. In most individuals, lung-recruited cells clear the infection, and the immune response retreats. However, in some cases, a dysfunctional immune response occurs, which triggers a cytokine storm in the lung, leading to acute respiratory distress syndrome (ARDS). Severe COVID-19 is characterized by an impaired innate and adaptive immune response and by a massive expansion of myeloid-derived suppressor cells (MDSCs). MDSCs function as protective regulators of the immune response, protecting the host from over-immunoreactivity and hyper-inflammation. However, under certain conditions, such as chronic inflammation and cancer, MDSCs could exert a detrimental role. Accordingly, the early expansion of MDSCs in COVID-19 is able to predict the fatal outcome of the infection. Here, we review recent data on MDSCs during COVID-19, discussing how they can influence the course of the disease and whether they could be considered as biomarker and possible targets for new therapeutic approaches.